Komunitas Anura (Amphibia) pada Tiga Tipe Habitat Perairan di Kawasan Hutan Harapan Jambi - Kharisma Putra; - Rizaldi; Djong Hon Tjong (Jurnal Biologi Universitas Andalas, 2012)
A study on Anuran’s community (Amphibia) living in three types of wetland habitats ( i.e: rivers, lakes, and swamp forest) at Harapan Rainforest Jambi was conducted from October 2011 to January 2012 by using Encounter Visual Survey along six belt transects. This study found 115 individuals of Anura’s, which belong to 14 species, eight genera, and three families. Density of each species was different between the three wetland habitats. The highest density in the rivers was Limnonectes paramacrodon (6.66 ind/ha), in the lakes was Occydozyga sumatrana (16.87 ind/ha), and in the swamp forest was Limnonectes paramacrodon (5 ind/ha). Diversity index of Shannon Wiener indicated that species diversity was different between lakes, rivers, and swamp forest (rivers: 1.227, lakes: 1.594, and swamp forest: 1.154). The highest similarity index was found between rivers and lakes (42.86%), and the lowest between swamp forest and lakes (16.67%). Distribution patterns of most Anuran’s species based on Quadrat Variance Analysis were clumped.Keywords: anura, community structure, distribution pattern, wetland habitat